Numerical analysis of the contact resistance in a no-insulation layer-wound coil with a simplified electromagnetic–mechanical model. (1st December 2022) - Li, Dongke; Tang, Yunkai; Liu, Donghui; Yong, Huadong
Abstract: An increase in the contact resistance of a no-insulation (NI) high-temperature superconducting coil was observed in high-field tests, which may be related to the mechanical deformation and the separation between adjacent turns in the coil. The large electromagnetic force generated in the high magnetic field can causeseparation between adjacent turns of the NI coil, which can affect the contact resistance of the magnet. An electromagnetic–mechanical model is built to study the effect of separation on the contact resistance and field delay time of an NI layer-wound coil. The numerical results show that the large electromagnetic force generated in the high field leads to the local separation between adjacent turns and the increase in contact resistance of the NI layer-wound coil. Moreover, a higher external field or target current can result in a larger area of separation, a higher contact resistance and a shorter characteristic field delay time. An overband can restrain the mechanical deformation and separation between turns of the NI coil in the high field, which suppresses the increase of turn-to-turn contact resistance.